Bibliometric analyses of turnover intention among nurses: implication for research and practice in China - Zhang, Huifang; Wong, Li Ping; Hoe, V. C. W. (Frontiers in Psychology, 2023)
Objective The aim of this study was to analyze the current status of research on nurses’ turnover intention and to provide suggestions and references for promoting research on turnover intention and for promoting hospital talent development. Methods We used the bibliometric method “turnover intention” or “intention to leave” and “nurse*” as subject terms, and 1543 articles from 2017 to 2021 were retrieved from the WoS database using VOSViewer and CiteSpace software. Article based on this descriptive statistical analysis was performed on the year of publication, region, institution, journal of publication, and cited articles. Results A total of 1,500 articles met the inclusion criteria. There is an overall upward trend in the number of articles published in the field of nursing in terms of turnover intention from 2017 to 2021. The United States has the highest number of publications and the highest number of institutions, while China ranks second in terms of publications, but there are no Chinese research institutions in the top 10. The top three journals in terms of the number of articles published are the Journal of nursing management, the Journal of advanced nursing, and the Journal of clinical nursing; Oman’s League had the highest number of citations for their article in 2021; the most frequently occurring keywords are burnout, stress, satisfaction, model, work environment, organizational commitment, perception, predictor, mental health, and mediating role. Conclusion There is a great need for further research on how to develop sound measures to tackle nurse turnover intention. The following improvements should be made, such as to enhance research institutional settings for nurses’ turnover intention in China and to increase attention to nurse burnout and possible mediating influences in future studies.